Pediatric COVID-19: Correlations between Clinical and Imaging Perspectives - Heba A. Ali; Shaimaa A. Mohammad (Pulmonary Medicine)
Background. Although SARS-CoV-2 infection primarily affects adults, the increasing emergence of infected pediatric patients has been recently reported. However, there is a paucity of data regarding the value of imaging in relation to the clinical severity of this pandemic emergency. Objectives. To demonstrate the relationships between clinical and radiological COVID-19 findings and to determine the most effective standardized pediatric clinical and imaging strategies predicting the disease severity. Patients and Methods. This observational study enrolled eighty pediatric patients with confirmed COVID-19 infection. The studied patients were categorized according to the disease severity and the presence of comorbidities. Patients’ clinical findings, chest X-ray, and CT imaging results were analyzed. Patients’ evaluations using several clinical and radiological severity scores were recorded. The relations between clinical and radiological severities were examined. Results. Significant associations were found between severe-to-critical illness and abnormal radiological findings (p=0.009). In addition, chest X-ray score, chest CT severity score, and rapid evaluation of anamnesis, PO2, imaging disease, and dyspnea-COVID (RAPID-COVID) score were significantly higher among patients with severe infection (p<0.001, <0.001, and 0.001) and those with comorbidities (p=0.005, 0.002, and <0.001). Conclusions. Chest imaging of pediatric patients with COVID-19 infection may be of value during the evaluation of severe cases of infected pediatric patients and in those with underlying comorbid conditions, especially during the early stage of infection. Moreover, the combined use of specific clinical and radiological COVID-19 scores are likely to be a successful measure of the extent of disease severity.